Riqueza de fungos micorrízicos arbusculares no solo e o crescimento inicial de espécies arbóreas nativas - Santos, José Geraldo Donizetti dos (2008)
The mechanisms that control and maintain diversity, primary productivity and plant community structure have not yet been completely elucidated. It has been suggested that the arbuscular mycorrhizal fungi (AMF) play an important role on plant communities, but a few experimental comprobatory evidence has been reported. In this study it was evaluated in five experiments, under greenhouse conditions, the role of AMF richness growth of individual and mixed the native wood species: Trema micrantha Blume, Schinus terebinthifolius Raddi, Senna macranthera (Vell.) Irw. & Barn. and Caesalpinia ferrea Mart. Four of these experiments were cultivated with these plant species individually and in a fifth one with plants species growing together, simulating a natural plant community. The following treatments were used: a non-mycorrhizal control (NI), inoculation with one (R1), two (R2), four (R4) and eight AMF species (R8) and a treatment with high P level (AP). Plant growth was favored both under AP treatment and mycorrhizal presence in contrast to NI. The increase in plant growth was associated with the increase in the AMF richness in the soil and the effect of fungal richness was more evident under plant species all together than as under individual growth. T. micrantha was the dominant species under species mixture condition without AMF inoculation, mainly in the AP treatment, where it accounted for more than 70% of total plant biomass. However, when AMF were present, the relative biomass yield was more evenly distributed, with a small dominance of S. terebinthifolius. Analyses of spore density and denaturing gradient gel electrophoresis (DGGE) of fungi rDNA small subunit (18S) amplified from DNA extracted of roots with primers NS31 and AM1 showed that changes in the soil fungi community altered root fungal community composition. Glomus clarum was the dominant species in the treatment R8, where Gigaspora margarita and Scutellospora heterogama were also prominent. Gigaspora margarita and Scutellospora heterogama were the dominant species in the treatment R4 and Gigaspora margarita was the dominant species when only two AMF species were present in the soil. Glomus etunicatum had an evident band in the DGGE gel only when it was the single species in the soil. The electrophoretic profiles of AMF colonizing the different hosts suggest the existence of preferential, plant-fungus relationship. This may reflect on the establishment capacity and competitiveness of the AMF species evaluated. In single growth conditions the increase in AMF richness improved the plant growth only up to four species in the soil, while in community conditions there was beneficial effect up to eight species. It is conclude that the mutual benefit of increasing the AMF richness is more important to plants growing in complex communities where plant competitiveness is high.